Analisis Variabel Makroekonomi terhadap Indeks Saham Kompas 100: Pendekatan VECM - Andani, Gina; Kurniawan, Mahrus Lutfi Adi (Journal of Advances in Accounting, Economics, and Management, 2024)
This study aims to determine the effect of world gold prices, interest rates, inflation, exchange rates, and the LQ45 Index on the stock price of the Kompas 100 index. This research was conducted using research data in 2015-2020 and analyzed using the Vector Error Correction Model approach. From the VECM estimation results, it is found that world gold prices, interest rates, inflation, exchange rates, and the LQ45 index affect the Kompas 100 index stock price in the long term. Meanwhile, in the short term, world gold prices, interest rates, inflation, exchange rates, and the LQ45 index have no effect on the stock price of the Kompas 100 index.